2022
DOI: 10.2460/ajvr.21.01.0007
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet-rich plasma effects on Staphylococcus aureus–induced chondrocyte death in an in vitro bovine septic arthritis model

Abstract: OBJECTIVE To investigate the chondroprotective effects of autologous platelet-rich plasma (PRP), ampicillin-sulbactam (AmpS), or PRP combined with AmpS (PRP+AmpS) in an in vitro chondrocyte explant model of bovine Staphylococcus aureus–induced septic arthritis. SAMPLE Autologous PRP and cartilage explants obtained from 6 healthy, adult, nonlactating Jersey-crossbred cows. ProcedureS Autologous PRP was prepared prior to euthanasia using an optimized double centrifugation protocol. Cartilage explants collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…One of the most recent investigations found that autologous bovine PRP had similar chondroprotective efficacy in Staphylococcus aureus-induced in vitro septic arthritis model to ampicillin-sulbactum. 12 If regenerative therapies prove to be an effective treatment modality, they would bypass the restrictions associated with local/systemic antimicrobial use in food-producing animals.…”
Section: Septic Arthritis Managementmentioning
confidence: 99%
“…One of the most recent investigations found that autologous bovine PRP had similar chondroprotective efficacy in Staphylococcus aureus-induced in vitro septic arthritis model to ampicillin-sulbactum. 12 If regenerative therapies prove to be an effective treatment modality, they would bypass the restrictions associated with local/systemic antimicrobial use in food-producing animals.…”
Section: Septic Arthritis Managementmentioning
confidence: 99%
“…Tsuzuki et al [ 15 ] described the positive regenerative effects of the use of gelatine microspheres incorporated with PRP and alginate in sole ulcers and has a beneficial effect on articular cartilage and ligament healing [ 16 , 17 , 18 ]). Moreover, the effectiveness of PRP has also been evaluated in in vitro studies regarding the chondroprotective effects of autologous PRP combined with antibiotics in septic arthritis caused by Staphylococcus aureus [ 19 ]. Regarding GFs, the amount released by PRP and the comparison of the concentrations of platelets and white blood cells in PRP’s layers and supernatant have been described [ 20 ], but the comparison of GFs release over time has not been investigated yet, as well as their exact antimicrobial role [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have investigated the in vitro effects of PRP [ 13 , 14 , 19 , 21 ], translating these findings into effective in vivo applications remains a subject of ongoing research and debate. The present study seeks to address this gap in the literature by systematically reviewing the existing body of knowledge regarding the in vivo utilisation of bovine PRP (PRP) within the same specimens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations